Hubungan Motivasi Dengan Kesiapan Mahasiswa Keperawatan Pada Pertolongan Pertama Korban Kecelakaan Lalu Lintas - Sari, Fani Puspita; Nirmalasari, Novita (Universitas Ivet, 2025)
One of the leading causes of injuries and fatalities globally, including in Yogyakarta's Special Region, is traffic accidents. Prompt handling through first aid is crucial to reducing mortality rates. As future healthcare providers, nursing students are expected to be able to apply emergency knowledge with optimal motivation and readiness. Assessing the connection between nursing students' interest and readiness to provide first assistance to victims of traffic accidents at Jenderal Achmad Yani University, Yogyakarta. The research used a quantitative design with a cross-sectional approach. Data collection was conducted using purposive sampling, adhering to the established inclusion and exclusion criteria, with a total sample of 55 respondents. Data were collected using a questionnaire on motivation to help traffic accident victims and readiness to provide first aid. Data analysis involved univariate and bivariate analysis using Somers’d test. The majority of nursing students have high motivation (61.8%) and are in the ready category (89.1%). The bivariate analysis results showed a p-value of 0.004 (p < 0.05) with a correlation coefficient of 0.405. There is a relationship between motivation and the readiness of nursing students in first aid for victims of traffic accidents at Jenderal Achmad Yani University, Yogyakarta.